Pengaruh Kepemimpinan Transformasional Kepala Sekolah Terhadap Disiplin Kerja Guru di SMP Negeri 1 Doloksanggul Tahun Ajaran 2025/2026 - Selly Nainggolan; Betty A.S Pakpahan; Tahoma F. Siburian; Endang J. Manullang; Abai Manupak Tambunan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT This study explains that the principal’s transformational leadership has been implemented in an effort to improve teachers’ work discipline at SMP Negeri 1 Doloksanggul. The purpose of this study is to determine the influence of the principal’s transformational leadership on teachers’ work discipline at SMP Negeri 1 Doloksanggul in the 2025/2026 academic year. The method used in this research is an inferential quantitative method. The population in this study consisted of all teachers of SMP Negeri 1 Doloksanggul, totaling 50 people, and this research used a population study. The research instrument was a closed questionnaire. The results of the data analysis show that there is a positive and significant influence of the principal’s transformational leadership on teachers’ work discipline, and the principal’s transformational leadership has been implemented at SMP Negeri 1 Doloksanggul in the 2025/2026 academic year. This is proven through the following data analysis: (1) Analysis prerequisite tests: (a) the normality test obtained an Asymp. Sig. (2-tailed) value of 0.200 > 0.05; (b) the linearity test obtained a significance value of deviation from linearity of 0.368 > 0.05. (2) Hypothesis testing: (a) the correlation test between variables X and Y obtained rxy = 0.323 > rtable = 0.279, indicating a positive relationship between variable X and variable Y; (b) the significance test obtained tcount = 2.363 > ttable = 2.021, indicating a significant relationship between variable X and variable Y; (c) the regression equation test obtained the regression equation Ŷ = 51.336 + 0.390X; (d) the coefficient of determination test (r²) = 10.4%; (e) hypothesis testing using the F test obtained Fcount > Ftable, namely 5.584 > 4.08. Thus, H0 is rejected and Ha is accepted, meaning that the study concludes that there is a positive and significant influence of transformational leadership on teachers’ performance at SMP Negeri 1 Doloksanggul in the 2025/2026 academic year, with a contribution of 10.4%. Transformational leadership itself is a leadership style that inspires and motivates members of an organization to achieve higher performance and organizational goals through vision, motivation, and positive change.